A contrastive view of adjectives in Croatian, Polish and English: subjectification as a local phenomenon - Stanojević, Mateusz-Milan (Array, 2011)
A study of English adjectives (Athanasiadou 2006) suggested that subjectification (defined as the degree to which the conceptualizer plays a role in construing the objective scene ; Langacker 2000) may be helpful in examining the various uses of adjectives in English. In this paper we attempt to do the same, comparing and contrasting three languages: English (as the point of reference), and Croatian and Polish. Croatian and Polish were selected because they allow relatively free combinations, with the caveat that Polish uses postposition for classifying senses. We examine whether subjectification may be taken as the organizing principle behind the prenominal, postnominal and predicative positions found in the three languages, i.e. whether the role of subjectification is global – working across constructions, or local – working within a construction. Examples from three languages showed that although subjectification does play a role in the various positions, it may not be taken as the organizing principle behind the differences. We argued that this was due to the fact that subjectification is a local phenomenon which works within a single construction, which is delimited formally and functionally. This is corroborated by other subjectified constructions. We believe that this is due to the gradual nature of subjectification, which requires recoverable links to previous stages.